Serum Leptin levels in ovarian polycystic disease and its correlation to body weight - Shalal, Maad M.; Miran, Najmah M.; Mahddi, Zina I. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Poly cystic ovary syndrome is a common disorder in women of  reproductive  age,  it  is associated  with  disturbance of  reproductive, endocrine  and  metabolic  functions. The pathophysiology of PCOS appears to be multifactorial and polygenic. Leptin seems to play an important role in pathophysiology of PCOS especially in women with BMI ≥25kg/m2.  J Fac Med Baghdad2014; Vol.56, No .2Received Sept .2013Accepted April. 2014Objectives:  To assess leptin level in both PCOS and healthy women and explore the relation to their body weight and body mass index.Patient and Methods: A total of 120 women were enrolled in this study, 60 women (50%) had PCOS (study group) and the reminder 60 women (50%) were healthy women and considered as control group. BMI was calculated first. Both groups were further subdivided into two groups; BMI of ≥25kg/m2 and BMI of